Alleviation mechanisms of metal(loid) stress in plants by silicon: a review. (21st June 2020) - Vaculík, Marek; Lukačová, Zuzana; Bokor, Boris; Martinka, Michal; Tripathi, Durgesh Kumar; Lux, Alexander
Abstract : We review currently known plant-based mechanisms by which silicon mitigates the toxic influence of various heavy metals and metalloids and improves plant growth and performance. Abstract: Silicon (Si), although not considered as an essential element for plants in general, can ameliorate the phytotoxicity induced by excess metal(loid)s whether non-essential (e.g. Cd, Pb, Cr, Al, As, and Sb) or essential (e.g. Cu, Ni, and Zn). The Si-enhanced resistance allowing plants to cope with this type of abiotic stress has been developed at multiple levels in plants. Restriction of root uptake and immobilization of metal(loid)s in the rhizosphere by Si is probably one of the first defence mechanism. Further, retention of elements in the root apoplasm might enhance the resistance and vigour of plants. At the cellular level, the formation of insoluble complexes between Si and metal(loid)s and their storage within cell walls help plants to decrease available element concentration and restrict symplasmic uptake. Moreover, Si influences the oxidative status of plants by modifying the activity of various antioxidants, improves membrane stability, and acts on gene expression, although its exact role in these processes is still not well understood. This review focuses on all currently known plant-based mechanisms related to Si supply and involved in amelioration of stress caused by excess metal(loid)s.